Potent antimicrobial activity of lipidated short alpha,gamma-hybrid peptides - Benke, Sushil N.; Thulasiram, Hirekodathakallu V.; Gopi, Hosahudya N. (ChemMedChem, 2017)
Herein we report the potent antimicrobial activity of alpha,gamma-hybrid lipopeptides composed of 1:1 alternating - and gamma-amino acids. Along with their potent antimicrobial activity against various Gram-positive and Gram-negative bacteria, these hybrid lipopeptides were found to be less hemolytic. Studies into the mechanism of action revealed that these short cationic lipopeptides bind and disrupt the bacterial cell membrane. Time-kill kinetics analyses revealed that the potent alpha,gamma-hybrid lipopeptides completely inhibit bacterial growth in less than 20 minutes. Overall, the promising antimicrobial activity along with lower hemolytic activity displayed by these alpha,gamma-hybrid lipopeptides make them well suited for further exploration into the design of potent lipopeptide antibiotics.